Study on Photophysical Properties of Novel Fluorescent Phenanthroimidazole-Thiadiazole Hybrid Derivatives - Zurnacı, Merve; Şener, İzzet; Gür, Mahmut; Şener, Nesrin (Springer Science and Business Media LLC, 2022)
Phenanthroimidazole-thiadiazole hybrid derivatives, which are new heterocyclic compounds with fluorescence properties, were synthesized by designing a two-step reaction mechanism and their photophysical properties were investigated. The synthesized derivatives were purified and their structures were elucidated by ATR-IR, 1H-NMR, elemental analysis and HR-MS methods. In the next stage of the study, the absorption and emission spectra of the synthesized new phenanthroimidazole-thiadiazole hybrid derivatives were determined by UV-Vis and fluorescence spectroscopy. Stokes' shifts, molar extinction coefficients (ε), singlet energy levels (Es), quantum yield (ϕf), lifetimes (τ), the radiative (kr) and the nonradiative (knr) constant for new hybrid derivatives were measured in DMSO. In addition, aggregation measurements, which is an important parameter that changes the photophysical properties were performed and for these compounds, structure: photophysical properties were discussed.
Keywords: 3. Good health